The Use Of Ceramic Product Derived From Non-Halal Animal Bone: Is It Permissible From The Perspective Of Islamic Law? - Mohd Mahyeddin Mohd Salleh; Nurdeng Deuraseh; Suhaimi Ab. Rahman; Shuhaimi Mustafa5; Mohammad AizatJamaludin; Irwan Mohd Subri; Yasmin Hanani Mohd Safian (Asian Economic and Social Society, 2024)
Indexed by ERA